Occurrence of Soluble Very High Molecular Weight Fibrinogen Complexes in Hypercoagulable States. An in vitro and in vivo Study on their Features - Serneri, G G equal-contrib; Gensini, G F; Abbate, R; Favilla, S (Thrombosis and Haemostasis, 1979)
The gel-chromatography of the beta-alanine precipitate of human plasma and of purified fibrinogen shows the presence of different classes of fibrinogen complexes. A first class of complexes is detectable in correspondence with the ascending branch of the fibrinogen peak (“shoulder” complexes or high molecular weight fibrinogen complexes, HMWFC). A second class of complexes at very high molecular weight is eluted at the void volume (peak 1 complexes or VHMWFC). Treatment of plasma or fibrinogen in vitro with thrombin induces the formation of both classes of complexes. Also thrombin infusion in rabbits induces an increase of both VHMWFC and HMWFC; pretreatment with heparin prevents these changes. In the detection of VHMWF 4% agarose and beta-alanine precipitation seem to be necessary for a good resolution of the chromatographic profile. VHMWFC are devoid of albumin, transferrin and immunoglobulins on radial immunodiffusion and their elution volume suggests a molecular weight over 1 million. They show a procoagulant activity; namely they accelerate the fibrinogen polymerization and increase the resistance of normal plasma to heparin. They also induce the formation of platelet aggregates, reversible in EDTA, when incubated without stirring with control PRP, but in Born apparatus in presence of ADP they show a slight antiaggregating activity. In normal healthy young volunteers (control group A) the average values were respectively 7.81 ± 3.53 mg% for VHMWFC and 12.19 ± 4.74 mg% for HMWFC. Both VHMWFC and HMWFC are increased in patients with hypercoagulable states (patients with history of myocardial infarction, MIP, with chronic cerebrovascular disorders, CVP, with acute thrombophlebitis and with subacute intravascular coagulation, cancer patients). The increase of VHMWFC and HMWFC is however different in the various groups of patients. An increase predominantly of VHMWFC (sometimes with normal HMWFC) is detectable in MIP and CVP, whereas in subjects with acute thrombophlebitis and with cancer a predominant increase of HMWFC associated with increased levels of FDP is detectable. The detection of VHMWFC represents a useful tool for the evaluation of hypercoagulable state, and their occurrence can cooperate to enhance hypercoagulability as VHMWFC possess procoagulant activity.